1901 Ariz. Sess. Laws 1251-52 - (:unkn) unknown (My University, 1901)
§§ 385, 386: Prohibited the carry on the person, or in saddlebags, of any pistol, dirk, dagger, slung-shot, sword-cane, spear, brass knuckles, Bowie-knife, or any other kind of knife manufactured for purposes of offense or defense.
Keywords: CARRY